FINANCIAL RESOURCES OF SMALL BUSINESSES: INTERNAL AND EXTERNAL FACTORS INFLUENCING THE SOURCES OF THEIR FORMATION - Naumkin V.A., (Scientific Journal of Pedagogy and Economics, 2020)
The development of small business is of great importance for the stable development of the economy of any country. Economically developed small business is the basis of the economy of a developed state, so many research papers are devoted to the study of small business problems. Small businesses, because of their size, are more flexible in responding to all changes in the economy and have a greater potential for development. Recently, according to statistics, there has been a decrease in investment activity in small businesses. In other words, small business has become less invested in fixed assets. The observed crisis phenomena in the economy exacerbate the problem of investment financing and confirm the relevance of research on this topic. According to the heads of small businesses, the main reason for weak investment is the lack of financial resources. There is a wide variety of sources of financial resources. Sources of financial resources of small businesses have their own characteristics. However, small businesses are limited in their choice of sources of financial resources, because not all existing sources of financial resources are available and can be actually used by small businesses. There are a lot of number of factors that determine the final version of the structure of sources of financial resources of a small business. The article highlights the main external and internal factors that determine the structure of the sources of financial resources of small business. Internal factors characterize specificity of the enterprise (the legal form of the business, the sectoral specifics of small business, the stage of the life cycle of a small business and the economic characteristics of the businesses), external – the specifics of the external economic environment and industry, condition of the labor market and unemployment rate, financial and credit policy, investment sphere. The author of the article comes to the conclusion that the stage of the life cycle is one of the most important factors that determine the structure of sources of financial resources of small enterprises, since at different stages of the life cycle, the structure of financial sources of an enterprise differs. Among external factors, the author puts the economic conditions in which a small business operates in the first place. In a stable economic situation, a small business will have access to a wide range of sources of financial resources. In an economic downturn, the availability of debt sources is sharply reduced, due to high risks of non-return of funds, in addition, there is a low investment activity of business. The article describes the influence of each factor.